Frostbite: Current status and advancements in therapeutics. (October 2020) - Joshi, Kumud; Goyary, Danswrang; Mazumder, Bhaskar; Chattopadhyay, Pronobesh; Chakraborty, Reshmi; Bhutia, Y.D.; Karmakar, Sanjeev; Dwivedi, Sanjai Kumar
Abstract: Frostbite is a severe ischemic injury which occurs due to the tissue vascular damage after sub-zero temperature tissue exposure. Deep frostbite can result in necrosis and may need amputation of affected tissue. Though a serious injury, it is not very well understood, and further scientific exploration is needed. This work explores the current understanding of the pathophysiology of frostbite. We reviewed the current status of the diagnostics, the drugs, the therapies and the surgical practices for prevention and management of frostbite. Advances in nanotechnology and drug delivery had improved the therapeutic outcomes significantly. This review also explored the latest advancements and researches done for development of newer therapeutics and diagnostics for frostbite care. Graphical abstract: Image 1 Highlights: Frostbite: Pathohysiology of injury and cellular processes involved in tissue damage. Techniques for better and accurate diagnosis of frostbite damage and its prevention and field management. Therapeutic options for management and treatment of frostbite. Developments of newer therapeutic modalities and surgical treatment options in frostbite. Future direction of research in frostbite treatment.